Produção e aplicação de corantes naturais na indústria de alimentos: uma análise sistemática da literatura - Couto, João Vitor Santos do (Universidade Federal de São Carlos, 2025)
Natural dyes can be obtained from plants, invertebrates or minerals, the most common being those of plant origin, such as roots, pulp, bark, leaves and wood, or from biological sources, such as fungi. Renewable and generally non-toxic, natural dyes from plants are an interesting alternative, but they have limited ranges of color and properties of use, in addition to depending on the seasonality and abundance of plant growth in that season. Dyes extracted from fungi can be grown in the laboratory, cheaply and quickly, using waste as raw material, and are therefore renewable, are also non-toxic and have a wider range of nuclei and properties than dyes of plant origin. The natural dye industry is growing mainly due to the increasing demand from consumers, who prefer healthier products produced with greater environmental awareness. Studies have revealed a great diversity of natural sources of dyes, with applications in different productive sectors. The large-scale application of natural dyes still brings many challenges, especially with regard to the sustainability of the supply of these new raw materials, sources of dyes, to the industry. In addition to the seasonality already mentioned, some interesting species are native, endemic and produced from byproducts of the agroindustry. In the past, the research group on Particulate Systems of the Department of Chemical Engineering at UFSCar studied the use of dried annatto powder as a coloring agent for sausages, replacing the so-called “haems”, a chemical compound that, when it reaches the intestine, can irritate or damage its cells, increasing the risk of cancer. Widely cultivated in northern Brazil, annatto is today a source of coloring commonly found in the dairy industry. This undergraduate thesis describes, in an informative manner, a scenario of the current situation of both the production and application of natural dyes in the food industry. The literature review showed that, despite advances and growing interest from industry and academia, there are still significant gaps in practical and applied knowledge about natural dyes, which makes the challenges in the area even more relevant. Issues such as instability in the face of light, oxygen and temperature, removal costs, color standardization and the possibilities of effectively replacing synthetic dyes are still challenges. In addition, studies indicate that consumer accessibility and the perception of added value to natural products are fundamental elements for solutions to be adopted on a large scale. However, these perceptions still vary greatly according to socioeconomic profile and geographic region, which reinforces the need for interdisciplinary and regional research on the subject.
Production and application of natural colors in the food industry: a systematic literature review
Keywords: Corantes naturais; Consciência ambiental; Urucum; Natural dyes; Environmental awareness; Annatto; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA